Metadiscoursal connectors in linguistics MA theses in English L1 & L2 - Burneikaitė, Nida (Kalbotyra, 2009)
It is now commonly agreed that written academic texts are dialogic and interactive. How do academic writers increase interactivity of discourse? How do they organise texts and communicate with readers? Text-connectors is one of the many metadiscoursal categories used by writers to arrange their arguments and involve their readers. This paper considers the use of text-connectors in the Master’s thesis genre in Linguistics and analyses 70 theses by native and non-native (Lithuanian) students of English. The aim of the study is to work out a methodological framework for the analysis of text-connectors in the MA thesis genre and to compare the frequencies of text-connectors in native speaker (L1) and non-native speaker (L2) English theses as well as with frequencies in other genres. The classification of text-connectors developed in the study includes nine functional categories: addition, attitude, concession, contrast/comparison, illustration, restatement, result, sequence and summary; the procedural considerations cover the problems of reflexivity, multifunctionality, clustering and double use of text-connectors; the comparison of L1 and L2 theses shows an enormous overuse of text-connectors in L2 texts.
Keywords: text-connectors; metadiscourse; reflexivity; MA thesis genre; L1 and L2